Planning suburbia: development density issues - Biddlecombe, Bob (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
The right of speculative developers and government officials to significantly modify the culture of its poorest and weakest citizens in order to amortise the land banks and squeeze an already overdeveloped city into its inadequate infrastructure, demonstrates a breathtaking arrogance. It may however demonstrate stupidity if, as in the 1980s, the long-term social cost of the strategy makes the economic growth of the previous decade meaningless. Unfortunately the people who will have to pay will not be those who profited from the boom.
Papers from practice
Keywords: Urban geography -- Ireland